Relationship between Soil and Water Characteristics in the Wetlands of Doon Valley - Kumar, Saurabh; Kumar, Pramod; Salim, Mohd (Indian Forester, 2017)
A wetland is an ecosystem distinguished by water that either covers or saturates the ground in the root zone for at least part of the year. Fresh water swamps are the unique ecosystem having very specific vegetation. Doon valley has many fresh water swamps due to its unique topography surrounded by lesser Himalaya and Siwalik range. This study was conducted to find the relationship between the soil and water characteristics in two wetlands (swamp forests) of Doon valley. Both the swamp forests were dominated by Shorea robusta. Canonical correlation analysis (CCA) was applied to find relationships between soil and water chemical parameters. CCA can be used as a multivariate statistical method to provide a detailed view of relationships between two correlated sets of water and soil properties. Both the forests have almost same physicochemical properties of soil and water. The relationship between variables of soil and water parameters were found to be weak (Canonical R= 0.54), although significant.The ecosystems of Karwapani and Golatappar were under anthropogenic pressures which directly or indirectly affect the soil and water quality. Due to the increasing pressures on wetlands and other forest ecosystems in Doon valley there is a need to monitor long term cumulative effects on forest soil and water quality.